“Sistema de seguridad e higiene industrial para la prevención de riesgos laborales en la empresa Serviauto z&m, Naranjal 2018”. - Juan Miguel, Zula Miñarcaja (2020)
In this degree work, a study was carried out on “INDUSTRIAL SAFETY AND SAFETY SYSTEM FOR THE PREVENTION OF LABOR RISKS IN THE SERVIAUTO Z&M COMPANY, NARANJAL 2018”, which allowed us to have a close, timely and accurate knowledge for the benefit and safety of organizations. In the introduction of the present research work, the same background of the organizations that originated from the industrial revolution is explained, generating a positive impact for the different companies around the world, which experienced the process of industrialization , from this, various aspects that led to occupational accidents and various risks that negatively affected workers' health and stability were generated in the different organizations worldwide. The state of the art begins with the antecedents that exist of this research, to give rise to concepts established by various authors that theoretically base each of the research variables and also a brief historical review of what the company is currently SERVIAUTO Z&M. The methodology establishes the type, techniques and instruments of research, essential for the present development, defining the population and sample object of study to which a survey is applied that allows obtaining timely information on which our research is based. In the final part, it is concluded through a proposal for the implementation of an Industrial Hygiene and Safety System applied to SERVIAUTO Z&M.